VO2slow component assessment along an incremental swimming protocol - Fernandes, R. J.; de Jesus, K.; Sousa, A.; de Jesus, K.; Ribeiro, J.; Vilas-Boas, J. P. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The present study analysed the oxygen uptake slow component (V02sc) of front crawl swimming along an incremental swimming protocol, using a multi-exponential function. Eleven well-trained swimmers (20.4±2.5 yrs, 1.80±0.06 m and 74.1±4.12 kg) performed a front crawl incremental protocol of 7x300 m until exhaustion (with increments of 0,05m/s and 30s rest intervals between steps). V02 was collected bxb using a portable gas analyzer {K4b2) connected to the new Aqua Trainer respiratory snorkel {both from Cosmed, Italy). V02sc was assessed using a double exponential regression model with exponential terms amplitudes, time delays and time constants representing the V02 kinetics fast (1) and slow (2) components. In addition, the calculation of the V02sc values through the fixed interval method was also conducted by subtracting the average V02 observed in the last 40s of each step by the average V02 observed in the 3rd m in of exercise. A paired T-test was used to compare both methods along the incremental test (p ~ 0.05). The multi-exponential model showed that the vo2SC was above 200 ml/min from the 5th until the 7th step of the incremental protocol, i.e., intensitiesabove the anaerobic threshold. Differences were observed in mean values of V02sc obtained by the mathematical modelling and the fixed interval method in every step of the protocol (P 5 0.05, d > 0. 76). lt was concluded that in well-trained front crawl swimmers V025c exists in a significant faction at exercise intensities above the anaerobic threshold. This means that at heavy and severe swimming intensities the higher work rates implied the recruitment of faster but more easily fatigable fibers, which could lead to less efficient processes, and consequently, to higher V025c mean values.